Innovation in sweet rice wine with high antioxidant activity: Eucommia ulmoides leaf sweet rice wine - Ren, Na; Gong, Weiwei; Zhao, Yichen; Zhao, De-gang; Xu, Yiwen (Frontiers in Nutrition, 2023)
Eucommia ulmoides leaves are dried leaves of Eucommia ulmoides Oliv., which are used for both medicine and food, and have high nutrional value. However, the utilization rate is very low. In this study, Eucommia ulmoides leaves superfine powder and glutinous rice were used for fermentation to develop a new health-care Eucommia leaf sweet wine. The fermentation processes were optimized, and the nutritional value was evaluated by analysis of metabolites, functional compositions, antioxidant capacity and antihyperglycemic, antihyperlipidemic, antihypertensive ability. Metabolic analysis demonstrated that Eucommia leaf sweet wine contains a large amount of up-regulated flavonoids. Moreover, the contents of free amino acids, polyphenols, flavonoids and polysaccharides were 55.0±0.37 μg/g, 150.0±0.43 μg/g, 729.0±0.11 μg/g, 4.25±0.03 μg/g, and 4.77±0.08 μg/g, respectively, they were 2.6, 6.8, 14.7, 6.3 and 120 times that of traditional sweet wine, respectively. In addition, antioxidant capacity in vitro revealed that Eucommia leaf sweet wine had strong DPPH, superoxide anion, hydroxyl radical scavenging and iron reducing capacity, which indicated that Eucommia leaf sweet wine had strong antioxidant ability. Futhermore, Eucommia leaf sweet wine can significantly inhibit α-amylase, α-glucosidase and angiotensin-converting enzyme (ACE) (p<0.05), and had high cholate binding capacity. In conclusion, this study developed a new Eucommia leaf sweet wine with strong antioxidant ability, which represented positive antihypertensive, antihyperglycimic, antihyperlipidemic effects in vitro. This work provided reference for improving the utilization of Eucommia ulmoides leaves and the overall benefit of Eucommia ulmoides industry.